Immunohistochemical Evaluation of Histological Change in a Chinese Milroy Disease Family With Venous and Skin Abnormities - Zhang, Sijia; Chen, Xihui; Yuan, Lijuan; Wang, Shuyan; Moli, Dangzhi; Liu, Shujuan; Wu, Yuanming (Frontiers in Genetics, 2019)
Background: Milroy disease (MD) is rare and autosomal dominant resulting from mutations of the vascular endothelial growth factor receptor-3 (VEGFR-3 or FLT4), which leads to dysgenesis of the lymphatic system. Methods: Here we report a Chinese MD family with 2 affected members of two generations. We identiﬁed the mutation of c.3075G>A in one allele of FLT4 in Chinese population firstly. The father and child presented lymphedema under knees both. Unfortunately, the child was premature delivered for a car accident of the mother and then died of asphyxia. Then we gathered the tissue of the lower-limb from the child with permission from the parents and ethic committee. We stained the tissue with lymphatic marker D2-40 and hematoxylin-eosin to explore the histological changes. Afterwards, we compare the results with a normal child who unfortunately died of premature delivery also. Results: It is firstly identified the mutation of FLT4: c.3075G>A in Chinese population, and the mutation Inherited in the lineage. The histological evaluation indicated: 1. The number of lymphatic vessels decreased; 2. The morphology and structure of lymphatic vessels was abnormal. And what is added to our knowledge: 1. Capillary hyperemia and phlebectasia is severe; 2. Vascular malformations; 3. The number of vascular endothelial cells and vascular smooth muscle cells decreased; 5. Large sheets of epidermis desquamated; 6. The numbers of cutaneous appendages reduced in MD. Conclusions: Based on the new findings, we assume that mutation of FLT4 not only affect the lymphogenesis, but also the angiogenesis and epidermis structure.